Injection enhanced SiC planar gate IGBT with partial Schottky contact emitter. (1st November 2021) - Zhang, Jinping; Tu, Yuanyuan; Luo, Junyi; Peng, Zhenfeng; Deng, Xiaochuan; Zhang, Bo
Abstract: A novel injection enhanced silicon carbide (SiC) planar gate insulated gate bipolar transistor with partial schottky contact emitter (PSE-IGBT) is proposed in this paper. The p-type schottky diode (p-SD) formed between the PSE and p-body region acts as a barrier to prevent the hole from flowing into the emitter, which enhances the conductivity modulation and optimizes the carrier distribution in the drift region in the conduction state. Therefore, compared with the conventional SiC IGBT (Con-IGBT), the device performance is significantly improved for the proposed structure. The simulation results show that the on-state voltage drop ( V ceon ) of the proposed SiC PSE-IGBT with the emitter metal of nickel (PSE-IGBT Ni ) and titanium (PSE-IGBT Ti ) is reduced from 6.61V of the SiC Con-IGBT to 5.83V and 5.48V, respectively. Meanwhile, the turn-off loss ( E off ) of the proposed SiC PSE-IGBT Ni and PSE-IGBT Ti is only 11.15 mJ/cm 2 and 9.80 mJ/cm 2, which is 47.5% and 53.9% lower than 21.25 mJ/cm 2 of the SiC Con-IGBT at the V ceon of 6.4V, respectively. Furthermore, turn-off capability at high temperature and large current is checked and no degradation of the turn-off capability is observed for the proposed SiC PSE-IGBTs.